HUMAN FACTORS AND ERGONOMICS ASSESSMENT OF MORTAR PREPARATION USING MIXERS (Fiep Bulletin - online, 2016)
This article aimed to analyze working conditions that builders face during filling mortar into mixers, using NR17. In order to provide more exact data RULA (Rapid Upper Limb Assessment) and REBA (Rapid Entire Body Assessment) techniques were used. In this research has been applied the study of multiple cases as main technique. Data were collected in six mid-size residential constructions, which are located in the city of Curitiba, State of Parana. It was counted on the participation of eight workers, who act as servants of masons. In this research the RULA and REBA tools were chosen. From a methodological point of view these techniques contributed the recommendations that can be taken to solve the problem diagnosed during the execution of tasks. Therefore, after data collection and application of ergonomic analysis with the support of RULA and REBA methods, it was noticed that the mortar mixers expose the workers with ergonomic inappropriate conditions such as awkward postures, use of muscle power and lifting the arms above the shoulders. Therefore, it is concluded that the analyzed construction sites need to adapt their equipment and workplace as recommended by Norm NR17, to prevent ergonomic problems, either removal of the workers.
Keywords: Ergonomics. Workplace safety. Mortar mixers.